Ultrasound‐Assisted Green Synthesis of 3, 5‐Disubstituted Isoxazole Secondary Sulfonamides via One‐Pot Five‐Component Reaction using CaCl2/K2CO3 as Pre‐Catalyst in Water. Issue 45 (5th December 2022) - Mahmoudi, Ayoub El; Tachallait, Hamza; Moutaoukil, Zakaria; Arshad, Suhana; Karrouchi, Khalid; Benhida, Rachid; Bougrin, Khalid
Abstract: Tandem one‐pot five‐component reaction involving saccharin, propargyl bromide, aldehyde, hydroxylamine hydrochloride, and non‐conjugated primary amine has been explored for a rapid and an efficient synthesis of isoxazole‐secondary sulfonamides. This novel multicomponent reaction involves one pot N‐propargylation of saccharin, oximation, and 1, 3‐dipolar cycloaddition, followed by an intermolecular ring‐opening reaction by N‐nucleophilic amine. This transformation is catalyzed by CaCl2 /K2 CO3 and activated under ultrasonic cavitation. The CaCl2 salt is reported for the first time as a new precatalyst and a chlorine source. We showed that ultrasound, using sonotrode, significantly improved the reaction compared to ultrasonic bath and magnetic stirring. The isoxazole‐secondary sulfonamides 6 a –r were obtained in good to excellent yields (75–96 %) and withing shorter reaction times (13–17 min). All the synthesized compounds were fully characterized by IR, MS‐ESI, 1 H NMR, 13 C NMR spectroscopy, X‐ray crystallography and HPLC analysis. Abstract : An efficient and simple one‐pot synthetic protocol has been developed for the synthesis of new 3, 5‐disubstituted isoxazole secondary sulfonamides by using CaCl2 salt as a novel chlorine source via 1, 3‐dipolar cycloaddition reaction in water as a green solvent under ultrasound cavitation.